DESIGN, SYNTHESIS, AND PHARMACOLOGICAL EVALUATION OF SOME NOVEL BIS-THIAZOLE DERIVATIVES - Borde, Ramesh M; B Jadhav, Satish; R Dhavse, Rahul; S Munde, Achut (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: A series of substituted 5,2-bis-thiazoles derivatives were synthesized by Hantzsch reaction and evaluated in vitro for antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus. Methods: 2-(4-(benzyloxy)phenyl)-4-methylthiazole-5-carbothioamide were synthesized and allowed to react with various Î±-haloketones to give 5,2-bis-thiazoles, i.e., 2-(4-(benzyloxy)phenyl)-4-methyl-5-(4-substituted thiazol-2-yl)thiazole derivatives in excellent yield. The synthesized compounds were characterized by spectroscopic methods as well as elemental analyses. They were screened for their antimicrobial activity using the agar diffusion method. Result: Literature survey reveals that the synthesis of 2-(4-(benzyloxy)phenyl)-4-methyl-5-(4-substituted thiazol-2-yl)thiazole, i.e., (5,2-Bis-thiazoles) derivatives (10a-e) was not reported. The entire compound exhibited mild to moderate antimicrobial activity. Conclusion: The antimicrobial results revealed that the synthesized derivatives have significant antimicrobial properties, and further, structureâ€“ activity relationship studies may develop more potent and less toxic molecule.